Healthy hearts: a cross-sectional study of clinical cardiovascular disease risk factors in Northern Colorado school children (1992–2013). Issue 1 (December 2015) - Nelson, Tracy; Puccetti, NaNet; Luckasen, Gary
Abstract Background Despite significant declines in cardiovascular disease (CVD), it remains the number one cause of death in the United States. Determining factors that may be associated with CVD risk at a young age may allow us to better prevent CVD deaths in the future. The purpose of this paper is to determine the prevalence of CVD risk factors among 4th grade children who participated in a community-wide CVD education program; as well as the association of these risk factors with weight status and the prevalence of CVD risk factors among family members. Methods The Poudre Valley Health Systems, Healthy Hearts Club has provided a cardiovascular screening program (1992–2013) to identify risk factors among students in six Northern Colorado school districts. There were 9, 694 children (mean age, 10.3 years, 50 % female) included. Data were collected cross-sectionally with objective measures of total and high-density lipoprotein cholesterol (HDL-C), blood pressure and body mass index (BMI). Surveys were filled out by the parent and/or legal guardian and included questions about risk factors among family members. Means and frequencies were compared using SPSS software version 22 (IBM, Inc.). Results There were a significant number of children with elevated risk factors, including 35 % with total cholesterol ≥ 170 mg/dl, 22 % with HDL-C < 40 mg/dl, 13 % with Non-HDL-C ≥ 145 mg/dL, 6 % and 7 % with systolic and diastolic blood pressure ≥ 120 mmHg, and ≥ 80 mmHg respectively, and 21 % with BMI ≥ 85 % for age and sex. All the risk factors increased significantly when comparing normal weight to overweight and obese children. Further, among children with zero risk factors, 32.2 % reported a family member (other than the child) being overweight, while 56.5 % reported such among those children with five or six risk factors. Conclusions Overall, the prevalence of CVD risk factors in these children is similar to national levels and these factors are meaningfully associated with overweight and obesity, both within the child as well as within the family. This data suggests CVD risk factor reduction and prevention must focus on overweight and obesity and not be done in isolation of the family.